Thin glitter powder and preparation method thereof
Through the combined structure of PET base film layer, laser coating layer, imprinted laser layer and aluminum-plated layer, the problem of existing gloss powder is solved, and thin gloss and high temperature resistance is improved. , meets market demand.
Patent Information
- Application Number
- CN202411147603.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-13
AI Technical Summary
The existing glitter powder products are generally thicker, and lack thin glitter powder products, which is difficult to meet market demand.
Using a combined structure of PET base film layer, laser coating layer, imprinted laser layer and aluminum-plated layer, thinning green onion powder is prepared through the specific ratio and process of laser coating, including laser coating made of hydroxyl-containing acrylic resin, Hydroxylated melamine formaldehyde resin, ethyl acetate, butanone and dibutyltin dilaurate are composed of, and thinner products are formed by molding and vacuum aluminum plating.
It has achieved thinning of the green onion powder, improved the gloss and high temperature resistance of the product, enhanced the laser brightness and flexibility, and met the market's demand for thin green onion powder.
Smart Images

Figure BDA0005002640010000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glitter powder, in particular to thin glitter powder and a preparation method thereof. Background Art
[0002] Glitter is a unique surface treatment material known for its ability to enhance the visual effect of products. It can make the decoration part present a layered three-dimensional sense, and its strong glittering properties also make the decorated items more colorful and eye-catching. Glitter can be applied to a variety of materials such as paper, cloth, wood, metal, leather, plastic and ceramics by injection, screen printing, coating, printing, spraying or spreading to create decorative or reflective special effects. This type of material is widely used in many industries such as holiday decorations, coatings, inks, leather products, fabric printing, paper product printing, cosmetics (such as nail polish and eye shadow), fabric trademarks, crafts, fashion accessories, decorative fabrics, gift packaging, textile printing and dyeing, resin crafts, glass crafts, craft candles, sporting goods, screen printing, toys, thermal transfer patterns and plastic products.
[0003] The traditional method of making glitter powder usually involves mixing a coating material containing resin with various dyes, and then applying it on a high-gloss substrate such as aluminum foil or PET film. It is then processed through a series of fine processes such as vacuum aluminum plating, color coating, high-temperature curing, strip cutting and powder screening. The glitter powder produced in this way has a variety of shapes and colors, including colorful powder, gold and silver powder, red, blue, green and purple color powder, laser powder, fantasy color powder, etc., and the shapes include quadrilaterals, hexagons, diamonds and long strips.
[0004] However, the glitter powder on the market is generally thick, and the particles are relatively large, and there is a lack of thin glitter powder products. In view of this situation, we have developed a thin glitter powder and a preparation method thereof to solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to provide a thin glitter powder and a preparation method thereof, so as to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A thin glitter powder comprises, from bottom to top, a PET base film layer, a laser coating layer, an embossed laser layer, and an aluminum-plated layer; the thickness of the PET base film layer is 6 μm; the laser coating layer is obtained by coating the laser coating on the PET base film layer and drying it in an oven; the embossed laser layer is obtained by molding the laser coating layer with a molding machine; and the aluminum-plated layer is obtained by vacuum aluminum-plating the embossed laser layer.
[0008] Furthermore, the laser coating comprises, by weight, 6 to 10 parts by weight of hydroxyl-containing acrylic resin, 70 to 78 parts by weight of hydroxylated melamine formaldehyde resin, 2 to 6 parts by weight of ethyl acetate, 5 to 9 parts by weight of butanone, and 5.6 parts by weight of dibutyltin dilaurate.
[0009] Furthermore, the hydroxyl-containing acrylic resin is obtained by copolymerization of methyl methacrylate, butyl acrylate, methacrylic acid, acrylic acid, N-acetoxymethyl acrylamide, hydroxyethyl methacrylate, and pentaerythritol acrylate.
[0010] Furthermore, the hydroxylated melamine formaldehyde resin is obtained by mixing melamine, formaldehyde and glycerol.
[0011] The present invention also provides a method for preparing thin glitter powder, comprising the following preparation steps:
[0012] (1) coating the laser coating on the PET base film layer, heating at 120° C. for 12 h, then heating at 140° C. for 12 h, and then introducing it into an oven, drying it at a temperature of 130 to 150° C. at a drying speed of 80 to 100 m / min, to obtain a PET film coated with the laser coating;
[0013] (2) Then, the PET film coated with the laser coating is embossed using a TSL machine at a plate roller temperature of 120° C., a pressure of 40 kg, and a tension of 15 kg to obtain an embossed laser layer;
[0014] (3) Using EM06 machine, vacuum aluminum is plated on the embossed laser layer to obtain an aluminum layer; the thickness of the aluminum layer is
[0015] (4) Cutting and rolling the product obtained in step (3) to obtain thin glitter powder.
[0016] Furthermore, the raw material ratio of the laser coating is as follows: 6 to 10 parts by mass of hydroxyl-containing acrylic resin, 70 to 78 parts by mass of hydroxylated melamine formaldehyde resin, 2 to 6 parts by mass of ethyl acetate, 5 to 9 parts by mass of butanone, and 5.6 parts by mass of dibutyltin dilaurate.
[0017] Furthermore, the preparation method of the hydroxyl-containing acrylic resin is as follows: in a light-proof and nitrogen atmosphere, 1 / 3 of the mixed monomer is stirred and mixed with 30 parts by mass of isopropanol for 1 to 2 hours, the temperature is raised to 82° C., 0.2 to 0.4 parts by mass of azoisobutyronitrile is added under reflux, and the reaction is kept warm for 15 minutes. At the same time, 0.2 to 0.4 parts by mass of azoisobutyronitrile and 2 / 3 of the mixed monomer are added dropwise, and the reaction is completed within 2 hours. After the reaction is kept warm for 20 minutes, 30 parts by mass of isopropanol and 0.2 to 0.4 parts by mass of azoisobutyronitrile are added, and the reaction is kept warm for 20 minutes. Then, the temperature is lowered to 70° C., and ammonia water is added dropwise until it is completely soluble in water to obtain a hydroxyl-containing acrylic resin.
[0018] Furthermore, the raw material components of the mixed monomer include, by weight: 30 parts by weight of methyl methacrylate, 14 to 16 parts by weight of butyl acrylate, 4 to 6 parts by weight of methacrylic acid, 9 to 11 parts by weight of acrylic acid, 9 to 11 parts by weight of N-acetoxymethyl acrylamide, 0.2 to 0.4 parts by weight of hydroxyethyl methacrylate, and 0.1 to 0.3 parts by weight of pentaerythritol acrylate.
[0019] Further, the preparation method of N-acetoxymethyl acrylamide is as follows: at room temperature, 10 to 11 parts by mass of hydroxylamine hydrochloride and 40 parts by mass of water are mixed, and then 32 parts by mass of 0.6 g / mL sodium hydroxide solution is dripped in a nitrogen atmosphere, and then the temperature is lowered to 0 to 5° C., and 0.25 g / mL of methyl methacrylate methanol solution is dripped, and after the dripping is completed, the temperature is raised to 25° C., and the mixture is stirred for 24 hours at this temperature, and then the methanol is removed by a rotary evaporator, and then a 5% hydrochloric acid solution is added to adjust the pH to 5 to 6, and the water is further removed by rotary evaporation, and then the filtrate is extracted 3 times with ethyl acetate and filtered and collected. liquid, and the filtrate was evaporated to remove ethyl acetate to obtain an intermediate; 10 parts by mass of the intermediate and 199 parts by mass of dichloromethane were stirred at room temperature for 20 to 40 minutes, and then 54 parts by mass of 0.08 g / mL sodium hydroxide solution were dropped, followed by adding 10.2 parts by mass of acetic anhydride, and stirred at room temperature for 24 hours, and then 30 parts by mass of deionized water were added, and dichloromethane was used for extraction three times, and the organic phase was collected, and then the organic phase was washed with a saturated sodium chloride solution, dried with anhydrous magnesium sulfate, and filtered, and the filtrate was collected, and the solvent was removed by a rotary evaporator to obtain N-acetoxymethyl acrylamide as a light yellow transparent oil.
[0020] Furthermore, the preparation method of the hydroxylated melamine formaldehyde resin is as follows: a formaldehyde aqueous solution with a mass fraction of 37% and melamine are mixed, the temperature is raised to 60°C, after the melamine is completely dissolved, the pH value of the solution is adjusted to 8-9, and then the temperature is raised to 70-90°C again, and the reaction is continued for 30 minutes, and the temperature is lowered to 50-70°C, glycerol is added, the pH value of the solution is adjusted to 6-7, and then the reaction is continued for 20 minutes, and the solution is cooled to room temperature to obtain a hydroxylated melamine formaldehyde resin; wherein the molar ratio of melamine, formaldehyde in the formaldehyde aqueous solution, and glycerol is 1:3.5:3.
[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0022] The thin glitter powder of the present invention comprises, from bottom to top, a PET base film layer, a laser coating layer, a stamped laser layer, and an aluminum-plated layer in sequence; the thickness of the PET base film layer is 6 μm; the laser coating layer is obtained by coating the laser coating on the PET base film layer and drying it in an oven; the stamped laser layer is obtained by molding the laser coating layer with a molding machine; the aluminum-plated layer is obtained by vacuum aluminum-plating the stamped laser layer; the raw material components of the laser coating include: hydroxyl-containing acrylic resin, hydroxylated melamine formaldehyde resin, ethyl acetate, butanone, and dibutyltin dilaurate; the hydroxyl-containing acrylic resin is obtained by copolymerizing methyl methacrylate, butyl acrylate, methacrylic acid, acrylic acid, N-acetoxymethyl acrylamide, hydroxyethyl methacrylate, and pentaerythritol acrylate; the hydroxylated melamine formaldehyde resin is obtained by mixing melamine, formaldehyde, and propylene glycol.
[0023] The PET base film layer of the present invention is changed from the previous 38μm and 50μm base film to 6μm, thereby achieving the thinning of the glitter powder.
[0024] The hydroxyl-containing acrylic resin of the invention is obtained by copolymerization of methyl methacrylate, butyl acrylate, methacrylic acid, acrylic acid, N-acetoxymethyl acrylamide, hydroxyethyl methacrylate and pentaerythritol acrylate. The high temperature resistance of the hydroxyl-containing acrylic resin is improved by adding pentaerythritol acrylate, and a plurality of acrylic acid, acrylate and acrylamide derivatives are introduced for copolymerization to form a hydroxyl-containing hyperbranched acrylic resin.
[0025] The hydroxylated melamine formaldehyde resin of the present invention increases the water solubility of the melamine formaldehyde resin and facilitates the uniform mixing of the hydroxylated melamine formaldehyde resin and the hydroxyl-containing acrylic resin. Meanwhile, after the laser coating is coated on the PET base film layer and heated at 120°C for 12 hours, and then heated at 140°C for 12 hours, the N-acetoxymethyl acrylamide on the hydroxyl-containing acrylic resin undergoes Lossen rearrangement under the catalysis of dibutyltin dilaurate to form an isocyanate group. The isocyanate reacts with the hydroxyl group on the hydroxylated melamine formaldehyde resin to crosslink. The hydroxylated melamine formaldehyde resin and the hydroxyl-containing acrylic resin form an interpenetrating network structure. The two resins have good compatibility, increase the number of crosslinking points, improve the crosslinking degree, and thus improve the glossiness. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the glitter powder prepared in the following examples are as follows:
[0028] Glossiness: The glossiness of the thinned glitter powder prepared in the embodiment and the comparative example was tested according to GB / T1743.
[0029] Laser brightness: The thinned glitter powder prepared in the embodiment and the comparative example was taken to observe its embossing pattern and laser brightness.
[0030] High temperature resistance: After heating the thinned glitter powder obtained in the embodiment and the comparative example at 200°C for 100 hours, the flexibility before and after heating was tested according to GB / T1731 and the flexibility reduction rate before and after heating was calculated; the flexibility reduction rate before and after heating = (flexibility before heating - flexibility after heating) * 100% / flexibility before heating
[0031] Example 1
[0032] A method for preparing thin glitter powder comprises the following preparation steps:
[0033] (1) coating the laser coating on the PET base film layer, heating at 120° C. for 12 h, then heating at 140° C. for 12 h, and then introducing it into an oven and drying it at 130° C. at a drying speed of 80 m / min to obtain a PET film coated with the laser coating;
[0034] (2) Then, the PET film coated with the laser coating is embossed using a TSL machine at a plate roller temperature of 120° C., a pressure of 40 kg, and a tension of 15 kg to obtain an embossed laser layer;
[0035] (3) Using EM06 machine, vacuum aluminum is plated on the embossed laser layer to obtain an aluminum layer; the thickness of the aluminum layer is
[0036] (4) Cutting and rolling the product obtained in step (3) to obtain thin glitter powder.
[0037] Furthermore, the raw material ratio of the laser coating is as follows: 6 parts by mass of hydroxyl-containing acrylic resin, 70 parts by mass of hydroxylated melamine formaldehyde resin, 2 parts by mass of ethyl acetate, 5 parts by mass of butanone, and 5.6 parts by mass of dibutyltin dilaurate.
[0038] Furthermore, the preparation method of the hydroxyl-containing acrylic resin is as follows: in a light-proof and nitrogen atmosphere, 1 / 3 of the mixed monomer and 30 parts by mass of isopropanol are stirred and mixed for 1 hour, the temperature is raised to 82° C., 0.2 parts by mass of azoisobutyronitrile is added under reflux, and the reaction is kept warm for 15 minutes. At the same time, 0.2 parts by mass of azoisobutyronitrile and 2 / 3 of the mixed monomer are added dropwise, and the dripping is completed in 2 hours. After continuing the heat preservation reaction for 20 minutes, 30 parts by mass of isopropanol and 0.2 parts by mass of azoisobutyronitrile are added, and the heat preservation reaction is continued for 20 minutes, and then the temperature is reduced to 70° C., and ammonia water is added dropwise until it is completely soluble in water to obtain a hydroxyl-containing acrylic resin.
[0039] Furthermore, the raw material components of the mixed monomer include, by weight: 30 parts by weight of methyl methacrylate, 14 parts by weight of butyl acrylate, 4 parts by weight of methacrylic acid, 9 parts by weight of acrylic acid, 9 parts by weight of N-acetoxymethyl acrylamide, 0.2 parts by weight of hydroxyethyl methacrylate, and 0.1 parts by weight of pentaerythritol acrylate.
[0040] Further, the preparation method of N-acetoxymethyl acrylamide is as follows: at room temperature, 10 parts by mass of hydroxylamine hydrochloride and 40 parts by mass of water are mixed, and then 32 parts by mass of 0.6 g / mL sodium hydroxide solution is dropped in a nitrogen atmosphere, and then the temperature is lowered to 0°C, and 0.25 g / mL of methyl methacrylate methanol solution is added dropwise. After the addition is completed, the temperature is raised to 25°C, and the mixture is stirred for 24 hours at this temperature, and then the methanol is removed by a rotary evaporator, and then a 5% hydrochloric acid solution is added to adjust the pH to 5, and the water is removed by rotary evaporation, and then the filtrate is collected after extraction with ethyl acetate for 3 times and filtration. The filtrate was evaporated to remove ethyl acetate to obtain an intermediate; 10 parts by mass of the intermediate and 199 parts by mass of dichloromethane were stirred at room temperature for 20 minutes, then 54 parts by mass of 0.08 g / mL sodium hydroxide solution were dropped, and then 10.2 parts by mass of acetic anhydride were added. After stirring at room temperature for 24 hours, 30 parts by mass of deionized water were added, and dichloromethane was used for extraction three times, the organic phase was collected, and then the organic phase was washed with a saturated sodium chloride solution, dried with anhydrous magnesium sulfate, filtered, and the filtrate was collected. The solvent was removed using a rotary evaporator to obtain light yellow transparent oily N-acetoxymethyl acrylamide.
[0041] Furthermore, the preparation method of the hydroxylated melamine formaldehyde resin is as follows: a formaldehyde aqueous solution with a mass fraction of 37% and melamine are mixed, the temperature is raised to 60°C, and after the melamine is completely dissolved, the pH value of the solution is adjusted to 8 and then the temperature is raised to 70°C again, and the reaction is continued for 30 minutes, the temperature is lowered to 50°C, glycerol is added, the pH value of the solution is adjusted to 6 and then the reaction is again carried out for 20 minutes, and the hydroxylated melamine formaldehyde resin is obtained; wherein the molar ratio of melamine, formaldehyde in the formaldehyde aqueous solution, and glycerol is 1:3.5:3.
[0042] Example 2
[0043] A method for preparing thin glitter powder comprises the following steps:
[0044] (1) coating a laser coating on a PET base film layer, heating at 120° C. for 12 h, then heating at 140° C. for 12 h, and then introducing the film into an oven and drying the film at 140° C. at a drying speed of 90 m / min to obtain a PET film coated with the laser coating;
[0045] (2) Then, the PET film coated with the laser coating is embossed using a TSL machine at a plate roller temperature of 120° C., a pressure of 40 kg, and a tension of 15 kg to obtain an embossed laser layer;
[0046] (3) Using EM06 machine, vacuum aluminum is plated on the embossed laser layer to obtain an aluminum layer; the thickness of the aluminum layer is
[0047] (4) Cutting and rolling the product obtained in step (3) to obtain thin glitter powder.
[0048] Furthermore, the raw material ratio of the laser coating is as follows: 8 parts by mass of hydroxyl-containing acrylic resin, 74 parts by mass of hydroxylated melamine formaldehyde resin, 4 parts by mass of ethyl acetate, 7 parts by mass of butanone, and 5.6 parts by mass of dibutyltin dilaurate.
[0049] Furthermore, the preparation method of the hydroxyl-containing acrylic resin is as follows: in a light-proof and nitrogen atmosphere, 1 / 3 of the mixed monomer and 30 parts by mass of isopropanol are stirred and mixed for 1.5 hours, the temperature is raised to 82° C., 0.3 parts by mass of azoisobutyronitrile is added under reflux, and the reaction is kept warm for 15 minutes. At the same time, 0.3 parts by mass of azoisobutyronitrile and 2 / 3 of the mixed monomer are added dropwise, and the reaction is completed in 2 hours. After continuing the heat preservation reaction for 20 minutes, 30 parts by mass of isopropanol and 0.3 parts by mass of azoisobutyronitrile are added, and the reaction is continued for 20 minutes. Then, the temperature is lowered to 70° C., and ammonia water is added dropwise until it is completely water-soluble to obtain a hydroxyl-containing acrylic resin.
[0050] Furthermore, the raw material components of the mixed monomer include, by weight: 30 parts by weight of methyl methacrylate, 15 parts by weight of butyl acrylate, 5 parts by weight of methacrylic acid, 10 parts by weight of acrylic acid, 10 parts by weight of N-acetoxymethyl acrylamide, 0.3 parts by weight of hydroxyethyl methacrylate, and 0.2 parts by weight of pentaerythritol acrylate.
[0051] Further, the preparation method of N-acetoxymethyl acrylamide is as follows: at room temperature, 10.5 parts by mass of hydroxylamine hydrochloride and 40 parts by mass of water are mixed, and then 32 parts by mass of 0.6 g / mL sodium hydroxide solution is dropped in a nitrogen atmosphere, and then the temperature is lowered to 3° C., and 0.25 g / mL of methyl methacrylate methanol solution is dropped. After the addition is completed, the temperature is raised to 25° C., and the mixture is stirred for 24 hours at this temperature, and then the methanol is removed by a rotary evaporator, and then a 5% hydrochloric acid solution is added to adjust the pH to 5.5, and the water is removed by rotary evaporation, and then the filtrate is collected after extraction with ethyl acetate for 3 times. liquid, and the filtrate was evaporated to remove ethyl acetate to obtain an intermediate; 10 parts by mass of the intermediate and 199 parts by mass of dichloromethane were stirred at room temperature for 30 minutes, then 54 parts by mass of 0.08 g / mL sodium hydroxide solution were dropped, and then 10.2 parts by mass of acetic anhydride were added, and after stirring at room temperature for 24 hours, 30 parts by mass of deionized water were added, and dichloromethane was used for extraction three times, the organic phase was collected, and then the organic phase was washed with a saturated sodium chloride solution, dried with anhydrous magnesium sulfate, filtered, and the filtrate was collected. The solvent was removed using a rotary evaporator to obtain N-acetoxymethyl acrylamide as a light yellow transparent oil.
[0052] Furthermore, the preparation method of the hydroxylated melamine formaldehyde resin is as follows: a formaldehyde aqueous solution with a mass fraction of 37% and melamine are mixed, the temperature is raised to 60°C, and after the melamine is completely dissolved, the pH value of the solution is adjusted to 8.5 and then the temperature is raised to 80°C again, and the reaction is continued for 30 minutes, the temperature is lowered to 60°C, glycerol is added, the pH value of the solution is adjusted to 6.5 and then the reaction is continued for 20 minutes, and the solution is cooled to room temperature to obtain a hydroxylated melamine formaldehyde resin; wherein the molar ratio of melamine, formaldehyde in the formaldehyde aqueous solution, and glycerol is 1:3.5:3.
[0053] Example 3
[0054] A method for preparing thin glitter powder comprises the following preparation steps:
[0055] (1) coating the laser coating on the PET base film layer, heating at 120° C. for 12 h, then heating at 140° C. for 12 h, and then introducing it into an oven and drying it at 150° C. at a drying speed of 100 m / min to obtain a PET film coated with the laser coating;
[0056] (2) Then, the PET film coated with the laser coating is embossed using a TSL machine at a plate roller temperature of 120° C., a pressure of 40 kg, and a tension of 15 kg to obtain an embossed laser layer;
[0057] (3) Using EM06 machine, vacuum aluminum is plated on the embossed laser layer to obtain an aluminum layer; the thickness of the aluminum layer is
[0058] (4) Cutting and rolling the product obtained in step (3) to obtain thin glitter powder.
[0059] Furthermore, the raw material ratio of the laser coating is as follows: 10 parts by mass of hydroxyl-containing acrylic resin, 78 parts by mass of hydroxylated melamine formaldehyde resin, 6 parts by mass of ethyl acetate, 9 parts by mass of butanone, and 5.6 parts by mass of dibutyltin dilaurate.
[0060] Furthermore, the preparation method of the hydroxyl-containing acrylic resin is as follows: in a light-proof and nitrogen atmosphere, 1 / 3 of the mixed monomer is stirred and mixed with 30 parts by mass of isopropanol for 2 hours, the temperature is raised to 82° C., 0.4 parts by mass of azoisobutyronitrile is added under reflux, and the reaction is kept warm for 15 minutes. At the same time, 0.4 parts by mass of azoisobutyronitrile and 2 / 3 of the mixed monomer are added dropwise, and the dripping is completed in 2 hours. After continuing the heat preservation reaction for 20 minutes, 30 parts by mass of isopropanol and 0.4 parts by mass of azoisobutyronitrile are added, and the heat preservation reaction is continued for 20 minutes. Then, the temperature is lowered to 70° C., and ammonia water is added dropwise until it is completely water-soluble to obtain a hydroxyl-containing acrylic resin.
[0061] Furthermore, the raw material components of the mixed monomer include, by weight: 30 parts by weight of methyl methacrylate, 16 parts by weight of butyl acrylate, 6 parts by weight of methacrylic acid, 11 parts by weight of acrylic acid, 11 parts by weight of N-acetoxymethyl acrylamide, 0.4 parts by weight of hydroxyethyl methacrylate, and 0.3 parts by weight of pentaerythritol acrylate.
[0062] Further, the preparation method of N-acetoxymethyl acrylamide is as follows: at room temperature, 11 parts by mass of hydroxylamine hydrochloride and 40 parts by mass of water are mixed, and then 32 parts by mass of 0.6 g / mL sodium hydroxide solution is dropped in a nitrogen atmosphere, and then the temperature is lowered to 5°C, and 0.25 g / mL of methyl methacrylate methanol solution is added dropwise. After the addition is completed, the temperature is raised to 25°C, and the mixture is stirred for 24 hours at this temperature, and then the methanol is removed by a rotary evaporator, and then a 5% hydrochloric acid solution is added to adjust the pH to 6, and the water is further removed by rotary evaporation, and then the filtrate is collected after extraction with ethyl acetate for 3 times and filtration. The filtrate was evaporated to remove ethyl acetate to obtain an intermediate; 10 parts by mass of the intermediate and 199 parts by mass of dichloromethane were stirred at room temperature for 40 minutes, then 54 parts by mass of 0.08 g / mL sodium hydroxide solution were dropped, and then 10.2 parts by mass of acetic anhydride were added. After stirring at room temperature for 24 hours, 30 parts by mass of deionized water were added, and dichloromethane was used for extraction three times, the organic phase was collected, and then the organic phase was washed with a saturated sodium chloride solution, dried with anhydrous magnesium sulfate, and then filtered, the filtrate was collected, and the solvent was removed using a rotary evaporator to obtain light yellow transparent oily N-acetoxymethyl acrylamide.
[0063] Furthermore, the preparation method of the hydroxylated melamine formaldehyde resin is as follows: a formaldehyde aqueous solution with a mass fraction of 37% and melamine are mixed, the temperature is raised to 60°C, and after the melamine is completely dissolved, the pH value of the solution is adjusted to 9 and then the temperature is raised to 90°C again, and the reaction is continued for 30 minutes, the temperature is lowered to 70°C, glycerol is added, the pH value of the solution is adjusted to 7 and then the reaction is again carried out for 20 minutes, and the solution is cooled to room temperature to obtain a hydroxylated melamine formaldehyde resin; wherein the molar ratio of melamine, formaldehyde in the formaldehyde aqueous solution, and glycerol is 1:3.5:3.
[0064] Comparative Example 1
[0065] The difference between Comparative Example 1 and Example 2 is that methyl methacrylate, butyl acrylate, methacrylic acid, acrylic acid, hydroxyethyl methacrylate and pentaerythritol acrylate are copolymerized to obtain the hydroxyl-containing acrylic resin; the other components, proportions and processes are the same as those of Example 2.
[0066] Comparative Example 2
[0067] The difference between Comparative Example 2 and Example 2 is that methyl methacrylate, butyl acrylate, methacrylic acid, acrylic acid, N-acetoxymethyl acrylamide and hydroxyethyl methacrylate are copolymerized to obtain the hydroxyl-containing acrylic resin; the other components, proportions and processes are the same as those of Example 2.
[0068] Comparative Example 3
[0069] The difference between Comparative Example 3 and Example 2 is that 6 to 10 parts by mass of hydroxyl-containing acrylic resin, 2 to 6 parts by mass of ethyl acetate, 5 to 9 parts by mass of butanone, and 5.6 parts by mass of dibutyltin dilaurate are used to prepare the laser coating; the other components, proportions and processes are the same as those in Example 2.
[0070] Comparative Example 4
[0071] The difference between Comparative Example 4 and Example 2 is that 6 to 10 parts by mass of hydroxyl-containing acrylic resin, 70 to 78 parts by mass of melamine formaldehyde resin, 2 to 6 parts by mass of ethyl acetate, 5 to 9 parts by mass of butanone, and 5.6 parts by mass of dibutyltin dilaurate are used to prepare the laser coating; the other components, proportions and processes are the same as those in Example 2.
[0072] Comparative Example 5
[0073] The difference between Comparative Example 5 and Example 2 is only step (1): The specific steps of step (1) are as follows: apply the laser coating on the PET base film layer, then introduce it into an oven, and dry it at a temperature of 130 to 150°C at a drying speed of 80 to 100 m / min to obtain a PET film coated with laser coating; the remaining components, proportions and processes are the same as those in Example 2.
[0074] Effect example
[0075] Table 1 below shows the performance analysis results of the thinned glitter powders of Examples 1 to 3 of the present invention and Comparative Example 1.
[0076] Table 1
[0077]
[0078] From the comparison of the experimental data of Examples 1 to 3 and Comparative Example 1 in Table 1, it can be found that the thinned glitter powder prepared in the examples has higher glossiness, high temperature resistance and better laser brightness.
[0079] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1, it can be found that the hydroxyl-containing acrylic resin obtained by copolymerization of N-acetoxymethyl acrylamide is used to prepare thin-type glitter powder, which has high gloss, high temperature resistance and good laser brightness; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2, it can be found that the hydroxyl-containing acrylic resin obtained by copolymerization of pentaerythritol acrylate is used to prepare thin-type glitter powder, which has good high temperature resistance; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Examples 3 / 4, it can be found that the hydroxylated melamine formaldehyde resin is used to prepare thin-type glitter powder, which has high gloss, high temperature resistance and good laser brightness; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5, it can be found that after applying the coating in step (1), heating is performed at 120°C for 12 hours and then heating is continued at 140°C for 12 hours, and the prepared thin-type glitter powder has high gloss, high temperature resistance and good laser brightness.
[0080] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A thin glitter powder, characterized in that: From bottom to top, it includes a PET base film layer, a laser paint layer, an embossed laser layer, and an aluminum-plated layer; the thickness of the PET base film layer is 6μm; the laser paint layer is obtained by coating the laser paint on the PET base film layer and drying it in an oven; the embossed laser layer is obtained by molding the laser paint layer with a molding machine; the aluminum-plated layer is obtained by vacuum aluminum-plating the embossed laser layer.
2. The thinned glitter powder according to claim 1, characterized in that: The laser coating comprises, by weight, 6 to 10 parts by weight of hydroxyl-containing acrylic resin, 70 to 78 parts by weight of hydroxylated melamine formaldehyde resin, 2 to 6 parts by weight of ethyl acetate, 5 to 9 parts by weight of butanone, and 5.6 parts by weight of dibutyltin dilaurate.
3. The thinned glitter powder according to claim 2, characterized in that: The hydroxyl-containing acrylic resin is obtained by copolymerization of methyl methacrylate, butyl acrylate, methacrylic acid, acrylic acid, N-acetoxymethyl acrylamide, hydroxyethyl methacrylate and pentaerythritol acrylate.
4. The thinned glitter powder according to claim 2, characterized in that: The hydroxylated melamine formaldehyde resin is obtained by mixing melamine, formaldehyde and glycerol.
5. A method for preparing thinned glitter powder according to any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: (1) coating the laser coating on the PET base film layer, heating at 120° C. for 12 h, then heating at 140° C. for 12 h, and then introducing it into an oven, drying it at a temperature of 130 to 150° C. at a drying speed of 80 to 100 m / min, to obtain a PET film coated with the laser coating; (2) Then, the PET film coated with the laser coating is embossed using a TSL machine at a plate roller temperature of 120° C., a pressure of 40 kg, and a tension of 15 kg to obtain an embossed laser layer; (3) Using EM06 machine, vacuum aluminum is plated on the embossed laser layer to obtain an aluminum layer; the thickness of the aluminum layer is (4) Cutting and rolling the product obtained in step (3) to obtain thin glitter powder.
6. The method for preparing thinned glitter powder according to claim 5, characterized in that: The raw material ratio of the laser coating is as follows: 6-10 parts by weight of hydroxyl-containing acrylic resin, 70-78 parts by weight of hydroxylated melamine formaldehyde resin, 2-6 parts by weight of ethyl acetate, 5-9 parts by weight of butanone, and 5.6 parts by weight of dibutyltin dilaurate.
7. The method for preparing thinned glitter powder according to claim 6, characterized in that: The preparation method of the hydroxyl-containing acrylic resin is as follows: in a light-proof and nitrogen atmosphere, 1 / 3 of the mixed monomers and 30 parts by weight of isopropanol are stirred and mixed for 1 to 2 hours, the temperature is raised to 82° C., 0.2 to 0.4 parts by weight of azoisobutyronitrile is added under reflux, the mixture is kept warm for reaction for 15 minutes, and 0.2 to 0.4 parts by weight of azoisobutyronitrile and 2 / 3 of the mixed monomers are added dropwise at the same time, the mixture is dropped after 2 hours, the mixture is kept warm for reaction for 20 minutes, 30 parts by weight of isopropanol and 0.2 to 0.4 parts by weight of azoisobutyronitrile are added, the mixture is kept warm for reaction for 20 minutes, the temperature is lowered to 70° C., and ammonia water is added dropwise until the mixture is completely dissolved in water to obtain the hydroxyl-containing acrylic resin.
8. The method for preparing thinned glitter powder according to claim 7, characterized in that: The raw material components of the mixed monomer include, by weight: 30 parts by weight of methyl methacrylate, 14-16 parts by weight of butyl acrylate, 4-6 parts by weight of methacrylic acid, 9-11 parts by weight of acrylic acid, 9-11 parts by weight of N-acetoxymethyl acrylamide, 0.2-0.4 parts by weight of hydroxyethyl methacrylate, and 0.1-0.3 parts by weight of pentaerythritol acrylate.
9. The method for preparing thin glitter powder according to claim 8, characterized in that: The preparation method of N-acetoxymethyl acrylamide is as follows: at room temperature, 10 to 11 parts by mass of hydroxylamine hydrochloride and 40 parts by mass of water are mixed, and then 32 parts by mass of 0.6 g / mL sodium hydroxide solution is dripped in a nitrogen atmosphere, and then the temperature is lowered to 0 to 5° C., and 0.25 g / mL of methyl methacrylate methanol solution is dripped, and after the dripping is completed, the temperature is raised to 25° C., and the mixture is stirred for 24 hours at the temperature, and then the methanol is removed by a rotary evaporator, and then a hydrochloric acid solution with a mass fraction of 5% is added to adjust the pH to 5 to 6, and the water is continuously removed by rotary evaporation, and then the filtrate is collected after extraction with ethyl acetate for 3 times and filtration. The filtrate was rotary evaporated to remove ethyl acetate to obtain an intermediate; 10 parts by mass of the intermediate and 199 parts by mass of dichloromethane were stirred at room temperature for 20 to 40 minutes, then 54 parts by mass of 0.08 g / mL sodium hydroxide solution were dropped, and then 10.2 parts by mass of acetic anhydride were added. After stirring at room temperature for 24 hours, 30 parts by mass of deionized water were added, and dichloromethane was used for extraction three times, the organic phase was collected, and then the organic phase was washed with a saturated sodium chloride solution, dried with anhydrous magnesium sulfate, and then filtered, the filtrate was collected, and the solvent was removed using a rotary evaporator to obtain light yellow transparent oily N-acetoxymethyl acrylamide.
10. The method for preparing thinned glitter powder according to claim 6, characterized in that: The preparation method of the hydroxylated melamine formaldehyde resin is as follows: a formaldehyde aqueous solution with a mass fraction of 37% and melamine are mixed, the temperature is raised to 60° C., after the melamine is completely dissolved, the pH value of the solution is adjusted to 8-9, the temperature is raised to 70-90° C. again, the reaction is continued for 30 minutes, the temperature is lowered to 50-70° C., glycerol is added, the pH value of the solution is adjusted to 6-7, the reaction is again carried out for 20 minutes, and the solution is cooled to room temperature to obtain the hydroxylated melamine formaldehyde resin; wherein the molar ratio of melamine, formaldehyde in the formaldehyde aqueous solution, and glycerol is 1:3.5:3.
